2009
DOI: 10.1111/igc.0b013e3181a8b950
|View full text |Cite
|
Sign up to set email alerts
|

The Nonsynonymous Single-Nucleotide Polymorphisms in Codon 31 of p21 Gene and the Susceptibility to Cervical Cancer in Chinese Women

Abstract: p21 Codon 31 with AGA (Arg) allele is a genetic risk factor of cervical SCC, and the increased risk is probably not caused by increasing host susceptibility to HR-HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Some other methods were also applied, such as direct sequencing, Taqman, and SNaPshot (Table 1). Overall, most studies indicated that the distribution of genotypes in controls was consistent with HWE with the exception of 6 studies[19],[26],[40],[43],[47],[59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other methods were also applied, such as direct sequencing, Taqman, and SNaPshot (Table 1). Overall, most studies indicated that the distribution of genotypes in controls was consistent with HWE with the exception of 6 studies[19],[26],[40],[43],[47],[59].…”
Section: Resultsmentioning
confidence: 99%
“…The leave-one-out sensitivity analysis indicated that no single study changed the pooled ORs qualitatively. Furthermore, the exclusion of 6 studies [19],[28],[40],[43],[47],[59], whose genotype distributions deviated from HWE, did not affect the results of the meta-analysis (OR = 1.16, 95% CI = 1.01 to 1.34, P = 0.0004).…”
Section: Resultsmentioning
confidence: 99%
“…20,26,27 It is widely believed that deviation from HWE may be due to genetic reasons including nonrandom mating or the alleles reflect recent mutations that have not reached equilibrium, as well as methodological reasons including biased selection of subjects from the population or genotyping errors. 46,47 Despite of the reasons of disequilibrium, the results of genetic association studies might be spurious if the distribution of genotypes in the control groups were not in HWE.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies indicated that the distribution of genotypes in the controls was consistent with HWE, except for 3 studies. 20,26,27 Quantitative Synthesis Table 2 lists the main results of this meta-analysis, and Figure 1 shows the association of CC risk with p21 polymorphism Ser31Arg in the recessive model. Overall, the variant genotypes (Arg/Arg and Arg/Ser) of Ser31Arg were not associated with CC risk, when compared with the wild- On the basis of the potential underestimation of the true effect of the polymorphism on the CC risk, we stratified these studies according to country (China, Korea, or other), matched controls (yes or not), study sample size (e200 or 9200 subjects), and HWE in the controls (yes or not).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Many groups have attempted to investigate the association between CDKN1A c.93C>A and cervical cancer risk, and highly conflicting results have been obtained thus far. For example, even in the same population, some studies showed that the A allele was associated with increased cervical cancer susceptibility [121], but some others demonstrated a decreased susceptibility associated with the same allele [122,123]. It was not entirely clear as to how the polymorphism affect cervical cancer susceptibility, but it was hypothesized that the polymorphism could affect the DNA binding affinity, and therefore functionality, of the protein.…”
Section: Cdkn1amentioning
confidence: 99%